2014
DOI: 10.1038/tp.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor antagonists ketamine and Ro25-6981 inhibit evoked release of glutamate in vivo in the subiculum

Abstract: Preclinical and clinical data have identified ketamine, a non-selective NMDAR (N-methyl-D-aspartate receptor) antagonist, as a promising medication for patients who do not respond to treatment with monoamine-based antidepressants. Moreover, unlike the current monoamine-based antidepressants, ketamine has a long-lasting effect already after a single dose. The mechanisms of ketamine action remain to be fully understood. Using a recently developed microelectrode array (MEA), which allows sub-second measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Furthermore, these subfields constitute an important target for psychotropic drug action. In fact, antidepressants have been found to exert a trophic effect on CA3 and DG subfields and recently, a reduction in the glutamate release in the subiculum has been related with the fast‐acting antidepressant effect of ketamine . In agreement with these data, lithium was found to act on the subicular complex and on the CA3 and DG subfields as well.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, these subfields constitute an important target for psychotropic drug action. In fact, antidepressants have been found to exert a trophic effect on CA3 and DG subfields and recently, a reduction in the glutamate release in the subiculum has been related with the fast‐acting antidepressant effect of ketamine . In agreement with these data, lithium was found to act on the subicular complex and on the CA3 and DG subfields as well.…”
Section: Discussionsupporting
confidence: 61%
“…While it is generally assumed that the majority of ketamine’s therapeutic properties result from actions at postsynaptic NMDARs [97], ketamine and other NMDAR-based therapeutics may also affect preNMDARs. For example, ketamine administered at antidepressant doses reduces evoked glutamate release in vivo measured in the subiculum and prelimbic area of the prefrontal cortex, and, while not directly demonstrated, these effects have been proposed to be mediated by preNMDARs [98]. Therefore, future studies are warranted to disambiguate how NMDAR-based therapeutics affect preNMDARs.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosine phosphorylation of NR2B in the spinal cord is associated with the central sensitization, increasing dorsal the horn excitability and facilitating the sensory input, which may be responsible for BCP [ 10 , 11 ]. Previous studies have demonstrated that NMDA receptor antagonists (such as ketamine) and NR2B-selective antagonists (such as ifenprodil and Ro25-6981) could exert potent analgesic effects in animal models of BCP [ 12 , 13 ]. However, these antagonists have also been shown to be associated with intolerable side effects, including memory impairment and psychotomimetic effects.…”
Section: Introductionmentioning
confidence: 99%